Chemical composition and antibacterial activities of essential oils from Zingiber spectabile Griff - Sivasothy, Yasodha; Awang, Khalijah; Ibrahim, Halijah; Thong, Kwai Lin; Fitrah, N.; Koh, X.P.; Tan, L.K. (Taylor & Francis, 2012)
The essential oils of the leaves and rhizomes of Zingiber spectabile Griff. were analyzed by capillary gas chromatography (GC) and GC–mass spectrometry (GC–MS) following the isolation by hydrodistillation. In total, 80 compounds were identified in its leaf and rhizome oils. Both oils were sesquiterpenic in nature but with distinctly different odors. The most abundant components in the leaf oil were β-caryophyllene (21.3%) and β-elemene (12.5%), whereas the rhizomes yielded an oil rich in zerumbone (59.1%). The antibacterial activities of both oils against multidrug-resistant strains and food-borne pathogens were evaluated by the disc diffusion assay and by determining their minimum inhibitory concentration (MIC) values. The leaf oil was inactive against all tested microorganisms, whereas the rhizome oil exhibited weak activity against Escherichia coli, Salmonella enteritidis, Salmonella typhi, Salmonella typhimurium, Shigella flexneri, Klebsiella pneumoniae, Pseudomonas aeruginosa and methicillin-resistant Staphylococcus aureus (MRSA).